A frequency-based wordlist of Japanese junior high school textbook vocabulary - Ryan Klinger (Vocabulary Learning and Instruction, 2025)
Several studies have examined the content of Japanese junior high school textbooks in relation to various frequency-based word lists such as the New General Service List (NGSL) (Browne et al., 2013) (e.g, Nakayama, 2022a,b) and the British National Corpus (BNC) (e.g, Wongsarnpigoon, 2018), and have identified potential issues in terms of lexical coverage and the repetition of vocabulary items. Considering the potential differences in individual textbook series and differences between frequency-based wordlists, it is worthwhile to evaluate the entirety of the Japanese Ministry of Education, Culture, Sports, Science and Technology (MEXT) approved junior high school textbooks (MEXT, 2024) in relation to multiple researched word lists including the NGSL, and the New JACET8000 (JACET, 2016) wordlist. To do so, a corpus of 18 textbooks from 6 publishers was analyzed using the software AntConc (Anthony, 2022) to generate a junior high school vocabulary wordlist sorted by the combined frequency and range of each item. While MEXT has advanced the target number of vocabulary items junior high school (JHS) students in Japan are expected to know entering high school to a range between 2,200 and 2,500 words (MEXT, 2019), the content of those words is relatively unknown. Thus, the aim of this study is to evaluate the content of the collective vocabulary items within the catalogue of MEXT approved JHS textbooks, by examining their range, frequency, and difference in ranking between the NGSL and JACET8000 wordlists. Additionally, the pedagogical applications derived from the analysis of a JHS textbook wordlist are discussed.